Potencial do óleo extraído de resíduos da filetagem de tilápia (Oreochromis niloticus) para produção de biodiesel - Carvalho, Guilherme Cleto de (2016)
The aims of this study were to evaluate the potential of the oil extracted from tilapia residues filleting for biodiesel production, select the one that presents the greatest potential for this purpose and characterize the obtained biodiesel to be neutralized or refined and analyzed according to their physicochemical and yield characteristics. For this, the crude heads, carcasses and offal which have undergone physical and chemical analysis and yield were extracted. For this, the crude oil was extracted from the heads, carcasses and guts, which have passed through physicochemical and yield analysis.For the statistical analysis, a completely randomized design was used with 3 treatments (head, carcass and viscera) and 5 replications.It was observed significant differences in the oils (P <0.05) being the viscera oil the one that showed higher yield although it presented the worst values for all evaluated indices. For this reason this oil was selected for further studies. In this new stage of the study the treatments were: neutralized crude oil and viscera refined oil with different volumes of NaOH 16%.It was adopted a completely randomized design, with a 2x3 factorial (types of oil x soda volumes) with 3 replications. The analyzed variables were acid value, saponification index, peroxide value and iodine value. It was also evaluated the performance of all the obtained biodiesel. It can be concluded that: among the filleting residues oil of tilapias, the one which is more suitable for biodiesel production, due to its high yield, was the viscera oil. The use of all stages of refining is indispensable, once the obtained index and the yield were greater in the biodiesel refined oil; the produced biodiesel from tilapia’s viscera oil meets the ANP standards and, therefore, it is adequate for use.